Team performance during vacuum-assisted vaginal delivery: video review of obstetric multidisciplinary teams - Brogaard, L.; Rosvig, L.; Hjorth-Hansen, K. R.; Hvidman, L.; Hinshaw, K.; Kierkegaard, O.; Uldbjerg, N.; Manser, T. (Frontiers in Medicine, 2024)
Introduction: Vacuum extraction is generally considered an operator-dependent task, with most attention directed towards the obstetrician's technical abilities(1-3)Little is known about the effect of the team and non-technical skills on clinical outcomes in vacuum-assisted delivery. This study aimed to investigate whether the non-technical skills of obstetricians were correlated with their level of clinical performance via the analysis of video recordings of teams conducting actual vacuum extractions. Methods: We installed between two or three video cameras in each delivery room at Aarhus University Hospital and Horsens Regional Hospital and obtained 60 videos of teams managing vacuum extraction. Appropriate consent was obtained. Two raters carefully reviewed the videos and assessed the teams' non-technical skills using the Assessment of Obstetric Team Performance (AOTP) checklist, rating all items on a Likert scale score from 1-5 (1=poor; 3=average; and 5=excellent). This resulted in a total score ranging from 18-90. Two different raters independently assessed the teams' clinical performance (adherence to clinical guidelines) using the TeamOBS-Vacuum-Assisted Delivery (VAD) checklist, rating each item (0=not done; 1=done incorrectly; and 2=done correctly). This resulted in a total score (low clinical performance: 0-59; average: 60-84; and high: 85-100). Results: Teams that received excellent non-technical scores had an 81% probability of achieving high clinical performance, whereas this probability was only 12% among teams with average nontechnical scores (p < 0.001). Teams with a high clinical performance often had excellent behavior in the non-technical items of "team interaction," "anticipation," "avoidance fixation," and "focused communication." Teams with a low or average clinical performance often neglected to consider analgesia,had delayed abandonment of the attempted vaginal delivery and insufficient use of appropriate fetal monitoring. Interrater reliability was high for both rater-teams, with an ICC for the non-technical skills of 0.83 (95% confidence interval [CI]: 0.71-0.88) and 0.84 for the clinical performance (95% CI: 0.74-0.90).Although assisted vaginal delivery by vacuum extraction is generally considered to be an operator-dependent task, our findings suggest that teamwork and effective team interaction play crucial roles in achieving high clinical performance. Teamwork helped the consultant anticipate the next step, avoid fixation, ensure adequate analgesia, and maintain thorough fetal monitoring during delivery.